Distribution and denomination in Papua New Guinea: a field method and its results. Issue 2 (3rd March 2020) - Pickles, Anthony J.
ABSTRACT: In highland Papua New Guinea wealth distribution after a windfall is typically concealed by the donor. This trend was made easier by the introduction of state-issued currency, such that wealth reckoning and especially distribution preferences are often shrouded in mystery. The researcher set out to learn how denomination structures those money transfers by employing a semi-structured interview method centered around hypothetical distributions based on everyday encounters. Across four tailored 'scenarios, ' fifteen Papua New Guinean participants dwelt on who to give money to, why, and under what conditions. Observations are made about the driving forces in distribution practices, the pecuniary conception of certain relationships' importance, and relationships that turn on local conceptions of how to capitalize on the way money operates, thus demonstrating the utility of a culturally sensitive quantitative methodology.